Factors Affecting Patient Portal Use Among Low-Income Pregnant Women: Mixed-Methods Pilot Study - Kim, Juhee; Mathews, Holly; Cortright, Lindsay M.; Zeng, Xiaoming; Newton, Edward (My University, 2018)
Background: Patient portals offer patients personalized and secure Web access to their medical information and enable patients to manage their health care online. However, there is a lack of information about patient acceptance and use of patient portals among low-income pregnant women. Objective: This formative research aims to assess the potential of a patient portal, MyChart, for improving prenatal health care and pregnancy outcomes, and identify the barriers and facilitators of MyChart use among low-income pregnant women. Methods: A mixed-methods study was conducted with a convenience sample of 18 low-income pregnant women comprising low- and high-risk patients enrolled in a prenatal clinic in eastern North Carolina. MyChart use, patient demographics, and pregnancy information were collected by reviewing electronic medical charts. Health literacy was measured. Reported use and attitudes toward MyChart were collected using a semi-structured interview. Results: Although 39% (7/18) of participants interviewed signed up for MyChart, only 22% (4/18) of them became active users. Another 33% (6/18) had never heard of MyChart or was unsure of how to access it. Users primarily accessed test results and appointment schedules. The main facilitating factors for patient portal use were information and motivation from health care providers and concerns about pregnancy due to a history of miscarriage. Reported barriers were lack of educational resources, lack of care provider encouragement, and technical difficulties possibly exacerbated by low health literacy. Participants also suggested improvements for MyChart, especially the provision of discussion-based support for pregnant women. Conclusions: The one-time verbal introduction of MyChart does not meet current patients’ needs. Data reveal the need for more consistent patient education and support programs, tailored to patients’ previous pregnancy histories. The clinic also needs to facilitate better provider-patient communication about the importance of MyChart use.
Keywords: patient portals; digital divide; pregnancy; poverty; health literacy